A long-chain nylon composition, its preparation method and its application
A long-chain nylon composition, combining bio-based polyamide resin with polyethylene or polypropylene and fillers, addresses the limitations of existing plastic pipes by enhancing toughness and mechanical properties, making it suitable for diverse applications.
Patent Information
- Application Number
- CN202111673669.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-12-31
AI Technical Summary
Existing plastic pipes exhibit poor toughness, impact resistance, uneven wall thickness, and easy deformation, limiting their performance in various applications such as building water supply, drainage, and industrial fluid transportation.
A long-chain nylon composition comprising bio-based polyamide resin, polyethylene or polypropylene resin, compatibilizer, and filler, prepared through a two-step mixing and extrusion process, enhancing toughness, dimensional stability, and dielectric properties.
The long-chain nylon composite material demonstrates significant toughness, low water absorption, excellent mechanical properties, and corrosion resistance, suitable for manufacturing pipes with improved performance in demanding environments.
Smart Images

Figure BDA0003453718380000011 
Figure BDA0003453718380000021 
Figure BDA0003453718380000131
Abstract
Description
Technical Field
[0001] The invention relates to a long-chain nylon composition, a preparation method and application thereof. Background Art
[0002] Plastic pipes have a solid position in the field of building water supply and drainage pipes, heating pipes, gas pipes, electric wire pipes, industrial pipes, submarine pipelines and other pipeline facilities with their unique properties. The development goal of "replacing steel with plastics" is also steadily advancing. From the initial PE pipes, PP pipes, and PVC pipes, to aluminum-plastic composite (PAP) pipes and cross-linked polyethylene (PEX) pipes, there are more than a dozen categories, each with its own advantages and disadvantages. Table 1 shows the commonly used pipes. Different applications have different requirements for pipes. As a water supply pipe, the material must have good water pressure resistance, frost resistance and heat resistance, non-toxicity and pollution-free, durability, and leakage resistance; as a drainage pipe, the material does not need to have high hygiene indicators, but good chemical stability. If used outdoors, it also needs good external load bearing capacity and flexibility; heating pipes are often used in cold areas, and the requirements for the material are high temperature resistance, cold resistance, thermoplasticity and high mechanical properties; gas pipe materials must have high stability, high temperature resistance, flame retardancy, and corrosion resistance. At the same time, long-distance transportation determines that the pipe must be able to bend and deform without breaking, and have good air tightness; as an electrical wire pipe, the material must be heat-resistant, pressure-resistant and fire-resistant.
[0003] Table 1: Common pipe types
[0004]
[0005]
[0006] At present, although plastic pipes are widely used in building water supply and drainage, electricity, optical cable sheathing, and industrial fluid transportation, there are some problems in the application process, such as relatively poor toughness, poor impact resistance, uneven pipe wall thickness, and easy deformation. They are still unable to completely lead the pipe market. The research and development of new technologies and new products, and the improvement and enhancement of the performance of new plastic pipes are still the focus of my country's plastics industry. Summary of the invention
[0007] In order to overcome the above defects in the prior art, the present invention provides a long-chain nylon composition, a preparation method thereof and its application. The composite material prepared from the long-chain nylon composition has significant toughness, low water absorption, excellent dimensional stability, good dielectric properties, and also has the advantages of good corrosion resistance, pressure resistance, oil resistance, cold resistance, small fuel expansion coefficient, etc., and is an ideal material for manufacturing water supply and drainage pipes and automobile oil pipes.
[0008] In one aspect, the present invention provides a long-chain nylon composition comprising the following components: 40-70 parts by weight of a bio-based long-chain polyamide resin, 20-45 parts by weight of a polyethylene resin or a polypropylene resin, 5-12 parts by weight of a compatibilizer and 1-5 parts by weight of a filler.
[0009] In some embodiments, the long-chain nylon composition may be calculated as 100 parts by weight.
[0010] In some embodiments, the bio-based long-chain polyamide resin may be a bio-based long-chain polyamide 5X resin, for example, one or more of PA510, PA511, PA512, PA513, PA514, PA515, PA516, PA517, and PA518.
[0011] The bio-based polyamide 5X resin refers to the raw material monomers of pentamethylenediamine and long-chain dibasic acid prepared by biological fermentation, such as:
[0012] The raw monomers of PA510 are pentamethylenediamine and sebacic acid prepared by biological fermentation;
[0013] The raw monomers of PA511 are pentamethylenediamine and undecanediic acid prepared by biological fermentation;
[0014] The raw monomers of PA512 are pentamethylenediamine and dodecanedioic acid prepared by biological fermentation;
[0015] The raw material monomers of PA513 are pentamethylenediamine and tridecanedioic acid prepared by biological fermentation;
[0016] The raw material monomers of PA514 are pentamethylenediamine and tetradecanedioic acid prepared by biological fermentation;
[0017] The raw monomers of PA515 are pentamethylenediamine and pentadecanedioic acid prepared by biological fermentation;
[0018] The raw monomers of PA516 are pentamethylenediamine and hexadecanedioic acid prepared by biological fermentation;
[0019] The raw monomers of PA517 are pentamethylenediamine and heptadecanedioic acid prepared by biological fermentation;
[0020] The raw material monomers of PA518 are pentamethylenediamine and octadecanoic acid prepared by biological fermentation.
[0021] In some embodiments, the bio-based long chain polyamide resin may meet one or more of the following parameters:
[0022] Relative viscosity is 1.8-2.7, preferably 2.1-2.6;
[0023] The terminal amino group content is 40-60mmol / kg;
[0024] The melting point is 170-320°C, preferably 180-230°C;
[0025] Biobased content is 43%-100%;
[0026] The moisture content is below 2000ppm;
[0027] The number average molecular weight is 40-55 kg / mol, preferably 50-55 kg / mol;
[0028] The molecular weight distribution is 1.8-2.1.
[0029] The relative viscosity is measured by the concentrated sulfuric acid method using an Ubbelohde viscometer. The biobased content can be measured using carbon 14, for example, by the biobased content detection standard method ASTM D6866.
[0030] In some embodiments, the bio-based long-chain polyamide resin is derived from Cathay (Jinxiang) Biomaterials Co., Ltd.
[0031] In some embodiments, the bio-based long-chain polyamide resin may be present in an amount of 40-55 parts by weight, such as 40 parts by weight, 47 parts by weight, or 55 parts by weight.
[0032] In some embodiments, the polyethylene resin is PE100S.
[0033] In some embodiments, the polyethylene resin can be purchased from PetroChina Company Limited.
[0034] In some embodiments, the polypropylene resin is PP212E.
[0035] In some embodiments, the polypropylene resin can be purchased from Borealis Corporation.
[0036] In some embodiments, the polyethylene resin or the polypropylene resin may be present in an amount of 32-40 parts by weight.
[0037] In some embodiments, the compatibilizer may be one or more of a polyolefin grafted maleic anhydride compatibilizer, a polyolefin grafted methyl acrylate compatibilizer, and a rubber elastomer grafted maleic anhydride compatibilizer. Among them, the polyolefin grafted maleic anhydride compatibilizer may be conventional in the art, such as PP-g-MAH, PE-g-MAH or POE-g-MAH. The polyolefin grafted methyl acrylate compatibilizer may be conventional in the art, such as POE-g-GMA. The rubber elastomer grafted maleic anhydride compatibilizer may be conventional in the art, such as EPDM-g-MAH.
[0038] In some embodiments, the content of the compatibilizer may be 10 parts by weight.
[0039] In some embodiments, the filler may be conventional in the art, such as one or more of carbon black, CaSO4 whiskers, talc, attapulgite, glass balls, and kaolin particles.
[0040] In some embodiments, the filler may be particles or powders, and the shapes of the particles include spheres, quasi-spheres, cakes, flakes, ribbons, needles, polygons, faceted shapes, or random shapes.
[0041] In some embodiments, the content of the filler may be 3 parts by weight or 5 parts by weight.
[0042] In some embodiments, the long-chain nylon composition includes the following components: 47 parts by weight of a bio-based long-chain polyamide resin, 40 parts by weight of a polyethylene resin, 10 parts by weight of a compatibilizer, and 3 parts by weight of a filler of CaSO4, for example, 47 parts by weight of PA510, 40 parts by weight of PE100S, 10 parts by weight of PE-g-MAH, and 3 parts by weight of CaSO4 whiskers.
[0043] In some embodiments, the long-chain nylon composition includes the following components: 40 parts by weight of a bio-based long-chain polyamide resin, 40 parts by weight of a polypropylene resin, 10 parts by weight of a compatibilizer, and 5 parts by weight of a filler of CaSO4, for example, 40 parts by weight of PA513, 40 parts by weight of PP212E, 10 parts by weight of PP-g-MAH, and 5 parts by weight of CaSO4 whiskers.
[0044] In some embodiments, the long-chain nylon composition includes the following components: 55 parts by weight of a bio-based long-chain polyamide resin, 32 parts by weight of a polyethylene resin, 10 parts by weight of a compatibilizer, and 3 parts by weight of a filler, for example, 55 parts by weight of PA516, 32 parts by weight of PE100S, 10 parts by weight of POE-g-MAH, and 3 parts by weight of CaSO4 whiskers.
[0045] In some embodiments, the long-chain nylon composition includes the following components: 47 parts by weight of a bio-based long-chain polyamide resin, 40 parts by weight of a polyethylene resin, 10 parts by weight of a compatibilizer, and 3 parts by weight of a filler, for example, 47 parts by weight of PA510, 40 parts by weight of PE100S, 10 parts by weight of PE-g-MAH, and 3 parts by weight of talc.
[0046] In some embodiments, the long-chain nylon composition includes the following components: 40 parts by weight of a bio-based long-chain polyamide resin, 40 parts by weight of a polypropylene resin, 10 parts by weight of a compatibilizer, and 5 parts by weight of a filler, for example, 40 parts by weight of PA513, 40 parts by weight of PP212E, 10 parts by weight of PP-g-MAH, and 5 parts by weight of talc.
[0047] In some embodiments, the long-chain nylon composition includes the following components: 55 parts by weight of a bio-based long-chain polyamide resin, 32 parts by weight of a polyethylene resin, 10 parts by weight of a compatibilizer, and 3 parts by weight of a filler, for example, 55 parts by weight of PA516, 32 parts by weight of PE100S, 10 parts by weight of POE-g-MAH, and 3 parts by weight of talc.
[0048] On the other hand, the present invention provides a method for preparing a long-chain nylon composite material, which comprises the following steps: mixing and extruding the components of the long-chain nylon composition to obtain the composite material.
[0049] In some embodiments, the mixing may include the following steps: mixing pre-extruded material A and material B, wherein material A is a mixture of the bio-based long-chain polyamide resin and 30-80wt% (e.g., 30wt%, 50wt%, 60wt%) of a compatibilizer, and material B is a mixture of the polyethylene resin or polypropylene resin, a filler, and the remaining compatibilizer, wherein the wt% refers to the percentage of the compatibilizer in the material A to the total mass of the compatibilizer in the long-chain nylon composition. The two-step mixing process in the art can make the prepared molded product have better performance than the one-step mixing process.
[0050] In some embodiments, the extrusion and pre-extrusion may be performed using a conventional extruder in the art, such as a twin-screw extruder or a single-screw extruder.
[0051] Wherein, expressed in terms of screw speed, the screw speed of the extruder may be 200-600 rpm, for example, 400 rpm.
[0052] Wherein, the extruder can have seven heating zones, and the temperatures of zones one to seven are 195-250°C, 255-300°C, 255-300°C, 255-300°C, 275-310°C, 275-310°C, 255-310°C, for example, 250°C, 275°C, 280°C, 280°C, 285°C, 285°C, 280°C.
[0053] Wherein, the head pressure of the extruder may be 0.2-0.4 MPa, for example 0.3 MPa.
[0054] In some embodiments, the extrusion further comprises one or more of the following steps: forming, cooling, drying and cutting.
[0055] In another aspect, the present invention provides a long-chain nylon composite material, which is prepared by the method for preparing the long-chain nylon composite material as described above.
[0056] On the other hand, the present invention provides a molded product, which comprises the long-chain nylon composite material as described above. For example, the molded product can be a pipe. The molded product prepared by the present invention, such as a pipe, has a tensile strength of more than 60 MPa, an elongation at break of 30-60%, a water absorption rate of less than 2.5%, a bending strength of more than 59 MPa before water absorption, and more than 50 MPa after 8 hours of water absorption, a longitudinal shrinkage rate of less than 4%, a ring stiffness of 2-6%, no damage and no penetration under different hydrostatic strengths; and an oxidation induction time of 100-200 min.
[0057] In another aspect, the present invention provides an application of the long-chain nylon composition, long-chain nylon composite material or molded product as described above in the fields of building water supply and drainage pipes, heating pipes, gas pipes, electric wire pipes, industrial pipes, and submarine pipeline facilities, for example, as drainage pipes or automobile oil pipes.
[0058] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0059] The positive and progressive effects of the present invention are:
[0060] The long-chain nylon composite raw material of the present invention has unique advantages, and the molding process is simple, and the plastic pipe can be obtained only through extrusion-winding molding. At the same time, a small amount of PE (PP) resin is used to modify PA, and the obtained long-chain nylon composite material has significant toughness, low water absorption, excellent dimensional stability, and good dielectric properties. Its comprehensive performance meets the application conditions, and it is light in weight and meets the demand for lightweight materials. In addition, it also has the advantages of good corrosion resistance, pressure resistance, oil resistance, cold resistance, small fuel oil expansion coefficient, etc., and is an ideal material for manufacturing water supply and drainage pipelines and automobile oil pipes. DETAILED DESCRIPTION
[0061] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications. The reagents and raw materials used in the present invention are all commercially available.
[0062] Source of raw materials:
[0063] PA510, PA513, and PA516 resin particles were purchased from Cathay (Jinxiang) Biomaterials Co., Ltd.; PE100S resin particles were purchased from China National Petroleum Corporation; PP212E resin particles are Borealis products; and the compatibilizer was purchased from Shanghai Jiayirong Polymer Co., Ltd.
[0064] Among them, PA510 resin particles: relative viscosity 2.51, terminal amino content 54mmol / kg, melting point 217℃.
[0065] PA513 resin particles: relative viscosity 2.38, terminal amino content 41mmol / kg, melting point 197℃.
[0066] PA516 resin particles: relative viscosity 2.13, terminal amino content 47mmol / kg, melting point 192℃.
[0067] Embodiment 1:
[0068] The product was prepared by weighing 47 parts by weight of PA510 resin particles, 40 parts by weight of PE100S resin particles, 10 parts by weight of PE-g-MAH and 3 parts by weight of CaSO4 whiskers. First, PA510 and 3 parts by weight of compatibilizer PE-g-MAH were mixed evenly and added to a twin-screw extruder to obtain resin slices; then, the obtained slices were added to a single-screw extruder together with PE100S, 7 parts by weight of compatibilizer PE-g-MAH and CaSO4 whiskers, and the materials were melt-mixed, extruded into filaments, cooled and hardened in a 30°C, 4m long cooling water bath, and hot-air dried to obtain an empty tube with an outer diameter of 500mm, which was cut into 6000mm long empty tube samples by a traction cutting machine. The temperatures of the seven heating zones of the twin-screw extruder and the single-screw extruder are 250 / 275 / 280 / 280 / 285 / 285 / 280 respectively, the die temperature is 270°C, the extruder head pressure is 0.2MPa, the feed speed is 20r / min, and the screw speed is 400r / min.
[0069] Embodiment 2:
[0070] The product was prepared by weighing 40 parts by weight of PA513 resin particles, 40 parts by weight of PP212E resin particles, 10 parts by weight of PP-g-MAH and 5 parts by weight of CaSO4 whiskers. First, PA513 and 5 parts by weight of compatibilizer PP-g-MAH were mixed evenly and added to a twin-screw extruder to obtain resin slices; then, the obtained slices were added to a single-screw extruder together with PP212E, 5 parts by weight of compatibilizer PP-g-MAH and CaSO4 whiskers, and the materials were melt-mixed, extruded into filaments, cooled and hardened in a 30°C, 4m long cooling water bath, and hot-air dried to obtain an empty tube with an outer diameter of 500mm, which was cut into 6000mm long empty tube samples by a traction cutting machine. The temperatures of the seven heating zones of the twin-screw extruder and the single-screw extruder are 250 / 275 / 280 / 280 / 285 / 285 / 280 respectively, the die temperature is 270°C, the extruder head pressure is 0.2MPa, the feed speed is 17r / min, and the screw speed is 400r / min.
[0071] Embodiment 3:
[0072] The product was prepared by weighing 55 parts by weight of PA516 resin particles, 32 parts by weight of PE100S resin particles, 10 parts by weight of POE-g-MAH and 3 parts by weight of CaSO4 whiskers. First, PA516 was evenly mixed with 6 parts by weight of compatibilizer POE-g-MAH, and added to a twin-screw extruder to obtain resin slices; then, the obtained slices were added to a single-screw extruder together with PE100S, 4 parts by weight of compatibilizer POE-g-MAH and CaSO4 whiskers, and the materials were melt-mixed, extruded into filaments, cooled and hardened in a 30°C, 4m long cooling water bath, and hot-air dried to obtain an empty tube with an outer diameter of 500mm, which was cut into 6000mm long empty tube samples by a traction cutting machine. The temperatures of the seven heating zones of the twin-screw extruder and the single-screw extruder are 250 / 275 / 280 / 280 / 285 / 285 / 280 respectively, the die temperature is 270°C, the extruder head pressure is 0.3MPa, the feed speed is 15r / min, and the screw speed is 400r / min.
[0073] Embodiment 4:
[0074] The product was prepared by weighing 47 parts by weight of PA510 resin particles, 40 parts by weight of PE100S resin particles, 10 parts by weight of PE-g-MAH and 3 parts by weight of talcum powder. First, PA510 and 3 parts by weight of compatibilizer PE-g-MAH were mixed evenly and added to a twin-screw extruder to obtain resin slices; then, the obtained slices were added to a single-screw extruder together with PE100S, 7 parts by weight of compatibilizer PE-g-MAH and talcum powder, and the materials were melt-mixed, extruded into filaments, cooled and hardened in a 30°C, 4m long cooling water bath, and hot-air dried to obtain an empty tube with an outer diameter of 500mm, which was cut into 6000mm long empty tube samples by a traction cutter. The temperatures of the seven heating zones of the twin-screw extruder and the single-screw extruder are 250 / 275 / 280 / 280 / 285 / 285 / 280 respectively, the die temperature is 270°C, the extruder head pressure is 0.2MPa, the feed speed is 20r / min, and the screw speed is 400r / min.
[0075] Embodiment 5:
[0076] The product was prepared by weighing 40 parts by weight of PA513 resin particles, 40 parts by weight of PP212E resin particles, 10 parts by weight of PP-g-MAH and 5 parts by weight of talcum powder. First, PA513 and 5 parts by weight of compatibilizer PP-g-MAH were mixed evenly and added to a twin-screw extruder to obtain resin slices; then, the obtained slices were added to a single-screw extruder together with PP212E, 5 parts by weight of compatibilizer PP-g-MAH and talcum powder, and the materials were melt-mixed, extruded into filaments, cooled and hardened in a 30°C, 4m long cooling water bath, and hot-air dried to obtain an empty tube with an outer diameter of 500 mm, which was cut into 6000 mm long empty tube samples by a traction cutter. The temperatures of the seven heating zones of the twin-screw extruder and the single-screw extruder are 250 / 275 / 280 / 280 / 285 / 285 / 280 respectively, the die temperature is 270°C, the extruder head pressure is 0.2MPa, the feed speed is 17r / min, and the screw speed is 400r / min.
[0077] Embodiment 6:
[0078] The product was prepared by weighing 55 parts by weight of PA516 resin particles, 32 parts by weight of PE100S resin particles, 10 parts by weight of POE-g-MAH and 3 parts by weight of talcum powder. First, PA516 was evenly mixed with 6 parts by weight of compatibilizer POE-g-MAH, and added to a twin-screw extruder to obtain resin slices; then, the obtained slices were added to a single-screw extruder together with PE100S, 4 parts by weight of compatibilizer POE-g-MAH and talcum powder, and the materials were melt-mixed, extruded into filaments, cooled and hardened in a 30°C, 4m long cooling water bath, and hot-air dried to obtain an empty tube with an outer diameter of 500mm, which was cut into 6000mm long empty tube samples by a traction cutting machine. The temperatures of the seven heating zones of the twin-screw extruder and the single-screw extruder are 250 / 275 / 280 / 280 / 285 / 285 / 280 respectively, the die temperature is 270°C, the extruder head pressure is 0.3MPa, the feed speed is 15r / min, and the screw speed is 400r / min.
[0079] Comparative Example 1
[0080] Weigh 95 parts by weight of PA510 resin particles and 5 parts by weight of CaSO4 whiskers and mix them evenly, add them into a twin-screw extruder, melt mix the materials, extrude the filaments, cool and harden them in a 30°C, 4m long cooling water bath, and dry them with hot air to obtain an empty tube with an outer diameter of 500mm, which is cut into 6000mm long empty tube samples by a traction cutter. The temperatures of the seven heating zones of the twin-screw extruder are 250 / 275 / 280 / 280 / 285 / 285 / 280, the die temperature is 270°C, the die pressure of the extruder is 0.4MPa, the feed speed is 20r / min, and the screw speed is 400r / min.
[0081] Comparative Example 2
[0082] Weigh 47 parts by weight of PA510 resin particles, 40 parts by weight of PE100S resin particles and 5 parts by weight of CaSO4 whiskers, mix them evenly, and add them to a single screw extruder. The materials are melt-mixed, extruded into filaments, cooled and hardened in a 30°C, 4m long cooling water bath, and dried with hot air to obtain an empty tube with an outer diameter of 500mm, which is cut into 6000mm long empty tube samples by a traction cutter. The temperatures of the seven heating zones of the single screw extruder are 250 / 275 / 280 / 280 / 285 / 285 / 280, respectively, the die temperature is 270°C, the extruder die pressure is 0.2MPa, the feed speed is 20r / min, and the screw speed is 400r / min.
[0083] Comparative Example 3
[0084] The product was prepared by weighing 47 parts by weight of PA510 resin particles, 40 parts by weight of PE100S resin particles and 10 parts by weight of PE-g-MAH. First, PA510 was evenly mixed with 3 parts by weight of compatibilizer PE-g-MAH and added to a twin-screw extruder to obtain resin slices; then, the obtained slices were added to a single-screw extruder together with PE100S and 7 parts by weight of compatibilizer PE-g-MAH, and the materials were melt-mixed, extruded into filaments, cooled and hardened in a 30°C, 4m long cooling water bath, and hot-air dried to obtain an empty tube with an outer diameter of 500mm, which was cut into 6000mm long empty tube samples by a traction cutter. The temperatures of the seven heating zones of the twin-screw extruder and the single-screw extruder are 250 / 275 / 280 / 280 / 285 / 285 / 280 respectively, the die temperature is 270°C, the extruder head pressure is 0.2MPa, the feed speed is 20r / min, and the screw speed is 400r / min.
[0085] Comparative Example 4
[0086] The product was prepared by weighing 47 parts by weight of PA66 resin particles, 40 parts by weight of PE100S resin particles, 10 parts by weight of PE-g-MAH and 3 parts by weight of CaSO4 whiskers. First, PA66 was evenly mixed with 3 parts of compatibilizer PE-g-MAH and added to a twin-screw extruder to obtain resin slices; then, the obtained slices were added to a single-screw extruder together with PE100S, 7 parts by weight of compatibilizer PE-g-MAH and CaSO4 whiskers, and the materials were melt-mixed, extruded into filaments, cooled and hardened in a 30°C, 4m long cooling water bath, and hot-air dried to obtain an empty tube with an outer diameter of 500mm, which was cut into 6000mm long empty tube samples by a traction cutting machine. The temperatures of the seven heating zones of the twin-screw extruder and the single-screw extruder are 250 / 275 / 280 / 280 / 285 / 285 / 280 respectively, the die temperature is 270°C, the extruder head pressure is 0.2MPa, the feed speed is 20r / min, and the screw speed is 400r / min.
[0087] Comparative Example 5
[0088] The product was prepared by weighing 80 parts by weight of PA510 resin particles, 7 parts by weight of PE100S resin particles, 10 parts by weight of PE-g-MAH and 3 parts by weight of CaSO4 whiskers. First, PA510 and 3 parts by weight of compatibilizer PE-g-MAH were mixed evenly and added to a twin-screw extruder to obtain resin slices; then, the obtained slices were added to a single-screw extruder together with PE100S, 7 parts by weight of compatibilizer PE-g-MAH and CaSO4 whiskers, and the materials were melt-mixed, extruded into filaments, cooled and hardened in a 30°C, 4m long cooling water bath, and hot-air dried to obtain an empty tube with an outer diameter of 500mm, which was cut into 6000mm long empty tube samples by a traction cutting machine. The temperatures of the seven heating zones of the twin-screw extruder and the single-screw extruder are 250 / 275 / 280 / 280 / 285 / 285 / 280 respectively, the die temperature is 270°C, the extruder head pressure is 0.2MPa, the feed speed is 20r / min, and the screw speed is 400r / min.
[0089] Comparative Example 6
[0090] The product was prepared by weighing 20 parts by weight of PA510 resin particles, 67 parts by weight of PE100S resin particles, 10 parts by weight of PE-g-MAH and 3 parts by weight of CaSO4 whiskers. First, PA510 and 3 parts by weight of compatibilizer PE-g-MAH were mixed evenly and added to a twin-screw extruder to obtain resin slices; then, the obtained slices were added to a single-screw extruder together with PE100S, 7 parts by weight of compatibilizer PE-g-MAH and CaSO4 whiskers, and the materials were melt-mixed, extruded into filaments, cooled and hardened in a 30°C, 4m long cooling water bath, and hot-air dried to obtain an empty tube with an outer diameter of 500mm, which was cut into 6000mm long empty tube samples by a traction cutting machine. The temperatures of the seven heating zones of the twin-screw extruder and the single-screw extruder are 250 / 275 / 280 / 280 / 285 / 285 / 280 respectively, the die temperature is 270°C, the extruder head pressure is 0.2MPa, the feed speed is 20r / min, and the screw speed is 400r / min.
[0091] Effect Example
[0092] The samples of Examples 1 to 6 and Comparative Examples 1 to 6 were cut into specimens of different sizes, which were used for ring stiffness determination, tensile test, longitudinal shrinkage determination, water absorption-bending performance, aging test, and long-term hydrostatic strength and thermal stability. The test results are shown in Tables 2 and 3 below.
[0093] 1. Ring stiffness test:
[0094] According to the test method of GB / T9647-2003, 300 mm long specimens were cut for ring stiffness test.
[0095] 2. Tensile strength and elongation at break test:
[0096] According to the requirements of GB / T8804-2003 standard, samples were cut from 150mm long pipe sections for tensile tests to test their tensile strength and elongation at break.
[0097] 3. Water absorption rate and bending strength test before and after water absorption:
[0098] The test refers to the standards ASTM-D570-2005, GB / T8361-2-1991 and GB / T9341-2008. First, a sample strip with a length of 80 mm, a width of 10 mm and a thickness of 4 mm was prepared, and its water absorption rate and bending performance before water absorption were tested, and then the bending performance was tested after 8 hours of water absorption.
[0099] 4. Longitudinal Retraction Test (TIR):
[0100] According to the requirements of GB / T6671-2001 standard, a 200mm long sample was cut to measure the longitudinal shrinkage rate.
[0101] 5. Oxidation induction time test:
[0102] According to the requirements of GB / T 17391-1998, 15 mg disc-shaped specimens were cut from the pipe for aging test to test the oxidation induction time.
[0103] 6. Hydrostatic strength and thermal stability test:
[0104] According to GB / T 6111-2002 standard, specimens with a length of 400 mm, an outer diameter of 25 mm, and a thickness of 2.3 mm were prepared to evaluate the long-term hydrostatic strength and thermal stability of the pipe.
[0105] Table 2
[0106]
[0107]
[0108] Table 3
[0109]
[0110] It can be seen from Tables 2 and 3 that the samples prepared by the present invention have the characteristics of significant toughness, low water absorption, excellent dimensional stability, excellent mechanical properties, anti-aging, excellent stiffness, etc., and the sample adopts an extrusion process, which can continuously produce pipes and has the characteristics of fast molding and high efficiency.
Claims
1. A long-chain nylon composition, characterized in that: It includes the following components: 40-70 parts by weight of a bio-based long-chain polyamide resin, 32-45 parts by weight of a polyethylene resin or a polypropylene resin, 5-12 parts by weight of a compatibilizer, and 1-5 parts by weight of a filler; Among them, the bio-based long-chain polyamide resin is bio-based long-chain polyamide 5X resin, the compatibilizer is one or more of polyolefin grafted maleic anhydride compatibilizers, polyolefin grafted methyl acrylate compatibilizers and rubber elastomer grafted maleic anhydride compatibilizers, and the filler is CaSO4 whiskers and / or talc powder.
2. The long-chain nylon composition according to claim 1, characterized in that The bio-based long-chain polyamide resin is one or more of PA510, PA511, PA512, PA513, PA514, PA515, PA516, PA517 and PA518; And / or, the content of the bio-based long-chain polyamide resin is 40-55 parts by weight.
3. The long-chain nylon composition according to claim 1 or 2, characterized in that The bio-based long-chain polyamide resin meets one or more of the following parameters: Relative viscosity is 1.8-2.7; The terminal amino group content is 40-60mmol / kg; Melting point is 170-320℃; Bio-based content is 43%-100%; The moisture content is below 2000ppm; The number average molecular weight is 40-55 kg / mol; The molecular weight distribution is 1.8-2.
1.
4. The long-chain nylon composition according to claim 1 or 2, characterized in that: The relative viscosity of the bio-based long-chain polyamide resin is 2.1-2.6; and / or, the melting point of the bio-based long-chain polyamide resin is 180-230° C.; and / or, the number average molecular weight of the bio-based long-chain polyamide resin is 50-55 kg / mol; And / or, the content of the bio-based long-chain polyamide resin is 40 parts by weight, 47 parts by weight or 55 parts by weight.
5. The long-chain nylon composition according to claim 1, characterized in that The polyethylene resin is PE100S; And / or, the polypropylene resin is PP212E; And / or, the content of the polyethylene resin or the polypropylene resin is 32-40 parts by weight; And / or, the compatibilizer is one or more of PP-g-MAH, PE-g-MAH, POE-g-MAH, POE-g-GMA and EPDM-g-MAH; And / or, the content of the compatibilizer is 10 parts by weight; And / or, the content of the filler is 3 parts by weight or 5 parts by weight.
6. A method for preparing a long-chain nylon composite material, characterized in that: It includes the following steps: The long-chain nylon composition according to any one of claims 1 to 5 can be obtained by mixing and extruding the components.
7. The preparation method according to claim 6, characterized in that: The mixing comprises the following steps: mixing the pre-extruded material A and material B, wherein the material A is a mixture of the bio-based long-chain polyamide resin and 30-80wt% of a compatibilizer, and the material B is a mixture of the polyethylene resin or the polypropylene resin, a filler and the remainder of the compatibilizer, and the wt% refers to the percentage of the compatibilizer in the material A to the total mass of the compatibilizer in the long-chain nylon composition.
8. The preparation method according to claim 7, characterized in that: The extrusion and pre-extrusion are carried out using a twin-screw extruder or a single-screw extruder.
9. The preparation method according to claim 8, characterized in that: Expressed in terms of screw speed, the screw speed of the extruder is 200-600 rpm; And / or, the extruder has seven heating zones, and the temperatures of zones 1 to 7 are 195-250°C, 255-300°C, 255-300°C, 255-300°C, 275-310°C, 275-310°C, and 255-310°C, respectively; And / or, the head pressure of the extruder is 0.2-0.4MPa; And / or, the extrusion further comprises one or more of the following steps: molding, cooling, drying and cutting.
10. The preparation method according to claim 9, characterized in that: The screw speed of the extruder is 400 rpm; And / or, the temperatures of the first to seventh zones are 250°C, 275°C, 280°C, 280°C, 285°C, 285°C, and 280°C, respectively; And / or, the head pressure of the extruder is 0.3 MPa.
11. A long-chain nylon composite material, prepared by the method for preparing the long-chain nylon composite material according to any one of claims 6 to 10.
12. A shaped article comprising the long-chain nylon composite material according to claim 11.
13. Use of the long-chain nylon composition according to any one of claims 1 to 5, the long-chain nylon composite material according to claim 11 or the molded product according to claim 12 in the fields of building water supply and drainage pipes, heating pipes, gas pipes, electric wire pipes or submarine pipeline facilities.
14. Use of the long-chain nylon composition according to any one of claims 1 to 5, the long-chain nylon composite material according to claim 11 or the molded article according to claim 12 in industrial pipes.
Citation Information
Patent Citations
Flame-retardant PP / nylon corrugated tube composite material and preparation method thereof
CN102050993A
Multilayer tube internal layer polymer composite material for automobile fuel pipes, and preparation method thereof
CN107936553A
